Dynamics of yield and chlorophyll content of four kangkung (Ipomea reptans Poir) sequences with soilless cultivation system due to direct and residual effects of vermicompost application - Nurhidayati,; Machfudz, Masyhuri; Ansari, Abu Saad; Pantipa Na Chiangmai, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The applications of organic fertilizers releasing nutrients slowly not only have a direct impact on the growing crop, but also, residual effects on the subsequent crops in the conventional crop cultivation systems. Studies on the residual effects of organic fertilizer in soilless crop cultivation are quite rare. The present study, which is a pot experiment conducted in a greenhouse, describes the dynamics of yield and chlorophyll content of kangkong as direct and residual effects of vermicompost for four consecutive plantings in soilless crop cultivation, further, compared with inorganic fertilizer treatment. The experimental design used was a randomized complete block design with different levels of vermicompost rates and a control treatment using inorganic fertilizer. The vermicompost was applied only in the first crop, while, inorganic fertilizer was supplemented in each crop. Fresh weight per plant per pot increases ~35 - 54% at the second planting compared with the first planting, thereafter, gradually decreases in subsequent planting. The content of chlorophyll A was found to be relatively constant, while the chlorophyll B content was highest in the first planting and, thereafter, subsequently decreased in further planting. The higher yields were found at 400 - 500 g pot-1 vermicompost fertilizer dose, insignificantly different from the inorganic fertilizers treatment.